Modulation of Retinal Atrophy With Rituximab in Multiple Sclerosis. (18th May 2021) - Lambe, Jeffrey; Risher, Hunter; Filippatou, Angeliki G.; Murphy, Olwen C.; Sotirchos, Elias S.; Ehrhardt, Henrik; Ogbuokiri, Esther; Pellegrini, Nicole; Toliver, Brandon; Luciano, Nicholas J.; Davis, Simidele; Fioravante, Nicholas; et al.
Abstract : Objective: To investigate the effects of rituximab on retinal atrophy in patients with relapsing-remitting multiple sclerosis (RRMS), we performed serial optical coherence tomography (OCT) scans among a cohort of patients with RRMS on rituximab and compared rates of ganglion cell + inner plexiform layer (GCIPL) atrophy to those observed among age- and sex-matched glatiramer acetate (GA)–and natalizumab-treated patients with RRMS and healthy controls (HCs). Methods: In this observational study, patients with RRMS treated with a single disease-modifying therapy and HCs were followed with serial OCT for a median duration of 2.8 years. Participants with uncontrolled hypertension, diabetes mellitus, or glaucoma, and eyes with optic neuritis ⩽6 months prior to baseline OCT, or during follow-up, were excluded. Statistical analyses were performed using linear mixed-effects regression. Results: During the overall follow-up period, rates of GCIPL atrophy were −0.28 ± 0.11 µm/y among rituximab-treated patients with RRMS (n = 35). This was similar to GA-treated (n = 49; −0.33 ± 0.05 µm/y; p = 0.69) and natalizumab-treated patients (n = 88; −0.17 ± 0.10 µm/y; p = 0.13) and faster than HCs (n = 78; −0.15 ± 0.03 µm/y; p = 0.006). Rituximab-treated patients exhibited 0.55 ± 0.23 µm/y faster rates of GCIPL atrophy during the first 12 months of treatment, relative to afterwards (n = 25; p = 0.02), during which period GCIPL atrophy rates were −0.14 ± 0.13 µm/y. Conclusions: Retinal atrophy in RRMS is modulated by rituximab. Greater attenuation of retinal atrophy may occur after 12 months of rituximab treatment, following which time GCIPL atrophy rates are similar to those observed among natalizumab-treated patients with RRMS and HCs. Our findings raise the possibility that the neuroprotective therapeutic response with rituximab in RRMS may take up to 12 months, which should be confirmed by larger studies. Classification of Evidence: This study provides Class IV evidence on the difference in rate of change of the GCIPL thickness in patients with RRMS comparing rituximab to other disease-modifying therapies.